Engaging minds : changing teaching in complex times - Davis, Brent; Sumara, Dennis J., 1958-; Luce-Kapler, Rebecca (New York : Routledge, 2008)
'Engaging Minds' involves readers in an exploration of teaching and learning. Prompting examinations of the complexities of learning, pedagogy, and schooling, it interrupts the assumptions and norms that frame popular understandings and refuses simplistic notions of unresolvable tensions.
First ed. published: Lawrence Erlbaum Associates, 2000.
Includes bibliographical references (p. [227]-234) and indexes.
Keywords: Learning; Teaching